Telaah Terhadap Ayat-Ayat yang Menggambarkan Fenomena Komersialisasi Agama Islam: Studi Tafsir Tematik - Tri Sandi; Sukiman; Nur Aisah Simamora (Jurnal test, 2025)
The phenomenon of commercialization of Islam has apparently occurred since the beginning of Islamic civilization, where the Qur’an, hadith and sharia law were exploited by individuals who justified any means to achieve their goals, namely worldly gain. This study is to answer the questions: (1) What are the verses in the Qur’an that explain the prohibition of commercialization of religion?, (2) How do the interpreters interpret the verses that prohibit commercialization of religion?, (3) What are the forms of commercialization of Islam throughout the exploration of the verses of the Qur’an?, (4) How is the relevance of the phenomenon of commercialization of religion to the lives of today’s people?. Several of these problems are discussed through library research with the maudhui interpretation method approach. The data sources in this study are the Qur’an as the primary source and interpretation books. All data are analyzed using a descriptive analysis approach. The results that the researchers found showed that there are nine verses in the Qur’an that seriously discuss the prohibition of commercialization of religion in the keyword tsamanan qoliilaa, be it changing, selling, exchanging the verses of Allah, false oaths, manipulating the truth and misleading the people. These actions will receive the same punishment as the Children of Israel and the Jewish priests, namely severe torture, humiliation and swallowing the embers of hellfire. Currently, this behavior can be carried out by ordinary people, money politics, manipulative influencers, businessmen who label sharia, academics and su’ scholars.